Asian monetary unit and monetary cooperation in Asia - Eiji Ogawa; Junko Shimizu (Asian Development Bank Institute (ADBI), 2011)
Regional monetary and financial cooperation in Asia has been discussed for years. To move towards a coordinated exchange rate policy, Ogawa and Shimizu (2005) proposed both an Asian Monetary Unit (AMU), which is a common currency basket computed as a weighted average of the thirteen ASEAN+3 currencies, and AMU Deviation Indicators (AMU DIs), which indicates the deviation of each Asian currency in terms of the AMU compared with the benchmark rate. The AMU and the AMU DIs are considered both as surveillance measures under the Chiang Mai Initiative and as benchmarks for coordinated exchange rate policies among Asian countries. In this paper, the authors show that monitoring the AMU and the AMU DIs plays an important role in the regional surveillance process under the Chiang Mai Initiative. By using daily and monthly data of AMU and AMU DIs for the period from January 2000 to June 2010, which are available from the website of the Research Institute of Economy, Trade, and Industry (RIETI), they examine their usefulness as a surveillance indicator. Our studies of AMU and AMU DIs confirm the following: first, an AMU peg system stabilizes the nominal effective exchange rate (NEER) of each Asian country. Second, the AMU and the AMU DIs could signal overvaluation or undervaluation for each of the Asian currencies. Third, trade imbalances within the region have been growing as the AMU DIs have been widening. Fourth, the AMU DIs could predict huge capital inflows and outflows for each Asian country. The above findings support the usefulness of using the AMU and the AMU DIs as surveillance indicators for monetary cooperation in Asia.
Keywords: F31; F33; F36; 330; Währungskorb; Wechselkurspolitik; Wirtschaftsintegration; Wechselkurs; Volatilität; Zahlungsbilanzungleichgewicht; Kapitalmobilität; Ostasien